Teknologi Informasi Dan Produktivitas Pada Industri Pengolahan Skala Mikro Kecil di Indonesia - yefita, angi; Edi Ariyanto; Maryanti (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
The objective of this research is to determine the influence of technology utilization on the productivity of micro and small manufacturing firms in Indonesia. In doing so, we explore the direct effects using company level data from the micro and small manufacturing firms survey data carried out by Indonesian Central Bureau of Statistics in 2019. To perform our empirical analysis, we estimate an ordinary least squares model by adding several control variables including financial access., workforce training, entrepreneur education and company age. Our main results uncover that the impact of technology utilitation components are significant and positive on labor productivity. Furthermore, there is also evidence that financial access, company age, entrepreneur education influence the productivity of micro and small manufacturing firms.